MTRR gene rs1801394 polymorphism is associated with neonatal birth weight in pregnant women with fetal growth retardation - Yu. N. Reshetnikova; I. V. Ponomarenko; V. М. Churnosov; M. S. Ponomarenko; M. I. Churnosov; E. A. Reshetnikov (Акушерство, гинекология и репродукция)
Aim: to assess associations between folate cycle gene polymorphism and neonatal birth weight in pregnant women with fetal growth retardation (FGR) and related functional effects in population of the Central Black Earth Region.Materials and Methods. 98 cases of women with FGR were enrolled to a retrospective molecular and genetic screening to assess prevalence 5 SNPs (single nucleotide polymorphisms) in genes involved in folic acid cycle and methionine metabolism (rs699517 TYMS, rs2790 TYMS, rs1979277 SHMT1, rs1805087 MTR, rs1801394 MTRR).Results. It was found out that allele A of the rs1801394 MTRR was associated with a lower neonatal birth weight (recessive model: β = –0.34 ± 0.13; p = 0.009). This polymorphic locus exerts crucial functional effects by determining the amino acid substitution in methionine synthase reductase (Ile22Met) localized in the region of modified histones, which mark enhancers and promoters in ectoderm, endoderm and mesoderm cell cultures, primary osteoblast cells, brain, fat nuclei, skeletal muscles, etc. In addition, rs1801394 MTRR is found DNA sites (motifs) responsible for sensitivity to transcription factors STAT and TBX5 being also related to MTRR gene mRNA expression level in subcutaneous and visceral adipose tissue, thyroid gland, fibroblast cell culture as well as various brain regions.Conclusion. Thus, the allele A of the rs1801394 polymorphism in MTRR gene is a risk factor for a lower neonatal birth weight.